Trajectory design and bandwidth allocation strategy in UAV-assisted MEC network - Xue JIANG; Liang ZHAO (物联网学报)
The unmanned aerial vehicle (UAV)-assisted mobile edge computing (MEC) network, where the UAV can be used as a mobile base station to collect data from the multiple user devices was studied.Since it should satisfy the UAV velocity constraint, the system computation latency constraint, and the system communication latency constraint, a joint scheme of bandwidth allocation and UAV 3D trajectory was proposed to minimize the total energy consumption of the network.The corresponding non-convex optimization problem that is difficult to solve was converted into two sub-optimization problems, which are the UAV 3D trajectory optimization subproblem by fixing bandwidth allocation, and the user equipment bandwidth allocation subproblem by fixing UAV 3D trajectory.Experiments demonstrate that the energy consumption of the proposed algorithm is less than that of the other two typical algorithms.Furthermore, the theoretical basis for solving the limited resource and energy problem in UAV-assisted MEC network was provided.